The Three Worlds of Economics - Reynolds, Lloud G. (Yale University Press, 1971)
In this splendid general review of the characteristics of the three major economics systems today (capitalist, socialist, less developed) and of the scope and method and teaching of economics from a world perspective$1! =s
Keywords: Economics; Non-Fiction